ä¸¹æˆŽå¸ƒæ‹‰å›½ç«‹å¤§å¦å¸ˆèŒƒå¦é™¢æ±‰è¯ä¸“ä¸š2016å±Šå¦ç”Ÿæ±‰è¯å¦ä¹ åŠ¨æœºè°ƒæŸ¥åˆ†æž - Nurhidayah, Utin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstrackIn learning foreign languages, learning motivation has a very important role and can encourage students in learning. Factors that affect students in learning a foreign language can be divided into intrinsic factors and extrinsic factors. Therefore, the authors conducted a research on the learning motivation of Teacher Training and Education Faculty of Tanjungpura University Mandarin Language education program students in the year 2016. The author analyzed the factors that influenced the learning motivation in Mandarin Language of 32 students. The intrinsic factors are divided into interests, initiative, self-ability, and attribution. Extrinsic factors are divided into teachers and tasks. Judging from the intrinsic factors, Mandarin students learning motivation is very good on the factor of "attribution". For example, although Mandarin is difficult, students will not give up learning it; when getting bad scores, students are willing to study harder. Judging from the extrinsic factors, Mandarin students learning motivation is very good on the "task" factor. Tasks can encourage students to learn. For example, if there are no assignments, students often do not have their own initiative to learn. Therefore the authors concluded that the observed students’ learning motivation in Mandarin Language is "very good". Keywords: Learning Motivation, Intrinsic Motivation, Extrinsic Motivation